Records of Early English Drama: A Retrospective - MacLean, Sally-Beth (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2014)
The Records of Early English Drama, founded in 1976, remains a productive humanities research project, with thirty-three volumes in print and two open access research and educational websites to date. This retrospective essay reflects on the individuals who contributed to its founding and evolution; the establishment of systematic research and editorial principles for an international team of contributors; the challenges of funding a collaborative enterprise with long term goals; some of its key contributions to the field of theatre history; and the transition from a print-based series to REED Online, a multi-faceted digital enterprise. In summary, while the re-envisioning of REED as an interoperable research and educational online resource represents a major shift in editorial and publication processes, the core values of the project remain intact: to work together in interdisciplinary collaboration with like-minded partners to deliver the results of systematic research in early theatre to as wide an audience as possible in the twenty-first century.